Nrf2 phosphorylation contributes to acquisition of pericyte reprogramming via the PKCδ pathway - Rika Sakuma; Yusuke Minato; Seishi Maeda; Hideshi Yagi (Neurobiology of Disease)
Pericytes (PCs) are vascular mural cells embedded in the basement membrane of micro blood vessels. It has been proposed using a C.B-17 mouse model of stroke that normal brain PCs are converted to ischemic PCs (iPCs), some of which express various stem cell markers. We previously reported that nuclear factor erythroid-2-related factor 2 (Nrf2) protected against oxidative stress following ischemia and promoted the PC reprogramming process. The present study examined the molecular mechanisms underlying the induction of Nrf2. We revealed that oxidative stress and pNrf2 induced by stroke proceeded the expression of nestin in meningeal cells and reactive PCs within the post-stroke area. PKCδ inhibitor treatment suppressed pNrf2 activation and restored the down-regulated expression of stem cell markers in iPCs in vitro. The PKCδ inhibitor treatment also suppressed the production of iPCs. These results suggest the potential of Nrf2 phosphorylation via PKCδ as a novel strategy for the treatment of ischemic injury.